(untitled) (Proceedings of the International Conference on Poverty and Sustainable Development, 2019)
Women enterprises are persistently increasing around the world and contributing to household income and overall national economies. They are playing an important role to promote sustainable practices in economics, social system and ecology, to perform sustainable development. Mutual Trust Bank Ltd. (MTB), a private commercial bank in Bangladesh is the line of activities for promoting women entrepreneurs’ development, providing credit facility and in addition given all types of support to promote women economic empowerment, as well as sustainable development of countries’ economic growth. MTB introduced a comprehensive credit product ‘MTB Gunabati’ jointly with SME Foundation (SMEF), a national organization works for SME development. The project aims to provide collateral free low-interest rate easy bank finance and other financial intermediaries to test inclusive lending models for women-owned micro, small and medium enterprises. MTB and SMEF jointly took the initiative to develop women entrepreneurship through financial inclusion at the micro and small enterprise level, what particular combination of different services such as, bank account opening, credit, savings and transactions. MTB implemented the credit project ‘MTB Gunabati’ especially designed for women entrepreneurs comprising others women entrepreneurship development initiatives and got the positive outcome proved towards sustainable development.